Severe Dumping Syndrome in a 6-year-old Girl with Congenital Microgastria Treated by Hunt-Lawrence Pouch - Filisetti, Claudia; Maestri, Luciano; Meroni, Milena; Marinoni, Federica; Riccipetitoni, Giovanna (European Journal of Pediatric Surgery Reports, 2017)
Microgastria is a rare congenital condition often associated with other anomalies. In the present report we describe the case of a 6-year-old girl with isolated CM who presented with dumping syndrome successfully treated by a Hunt-Lawrence pouch.
Keywords: congenital microgastria; dumping syndrome; Hunt-Lawrence pouch